Visceral leishmaniasis caused by Leishmania infantum in a Spanish patient in Argentina: What is the origin of the infection? Case report - Martín-Sánchez, Joaquina (2004)
Fil: Martín-Sánchez, Joaquina. Universidad de Granada. Departamento de Parasitología; España.